2016
DOI: 10.1177/2010105816674738
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and influence of home literacy environment in early childhood-centered literacy orientation

Abstract: Background: The home literacy environment (HLE) and joint parent-child book reading are key factors in children's language and literacy acquisition. Child-centered literacy orientation (CCLO) refers to the child's level of engagement in literacy events. Aim: To describe the HLE and identify demographic and HLE variables associated with a poor CCLO at 12 months of age. Methods: Parents of Singaporean children enrolled in the Growing Up in Singapore Towards healthy Outcomes (GUSTO; n = 1152, birth cohort 2009-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
(107 reference statements)
0
10
0
2
Order By: Relevance
“…These results agree with those described in previous research. For instance, Yeo et al (2014) have noted the influence of the mother tongue on the reading skills of children aged 6, and Mascarenhas et al (2017) have shown how the mother tongue of caregivers of a 12-month-old child is a measure that, among others, may influence their later reading development. This circumstance is compounded when added to low socioeconomic status (Davis et al, 2016;Marcella, Howes, & Fuligni, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results agree with those described in previous research. For instance, Yeo et al (2014) have noted the influence of the mother tongue on the reading skills of children aged 6, and Mascarenhas et al (2017) have shown how the mother tongue of caregivers of a 12-month-old child is a measure that, among others, may influence their later reading development. This circumstance is compounded when added to low socioeconomic status (Davis et al, 2016;Marcella, Howes, & Fuligni, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of the home literacy environment for children's reading development has been the subject of several studies over the last 20 years, as reflected in recent papers by Hofslundsengen, Gustafsson, and Hagtvet (2018), Marsh, Hannon, Lewis, and Ritchie (2015), Mascarenhas et al (2017) and Neumann (2016), among others. Parents' engagement in literacy activities at home has been pointed to be relevant to children's reading comprehension (Baker & Scher, 2002) as well as to their interest in reading and print (Weigel et al, 2006).…”
Section: Reading Comprehension and Literacy Interfacementioning
confidence: 99%
See 3 more Smart Citations